Trends in the Systematics of Bacteria and Fungi 2020
DOI: 10.1079/9781789244984.0168
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Genomic Taxonomy.

Abstract: This book chapter argues for an open-access catalogue of taxonomic descriptions with prototypes; diagnostic tables; and links to culture collections, to genome and gene sequences, and to other phenotypic and ecological databases. Ideally, the open access taxonomy will be based solely on genome sequences that allow both the phylogenetic allocation of new strains and species in the taxonomic space and the phenotypic/metabolic characterization in open online databases. Careful and thorough annotation of the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…Genome-to-genome distance was calculated using the Genome-to-genome distance calculator (GGDC) (Meier-Kolthoff et al 2013). The parameters used for the delimitation of a new species are less than 95% (AAI/ANI) and less than 70% GGDH with their closest neighbors, in conformity with the method previously described (Thompson et al 2013;De Vos et al 2017). Useful in silico phenotypes analyses were performed as previously described (Amaral et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Genome-to-genome distance was calculated using the Genome-to-genome distance calculator (GGDC) (Meier-Kolthoff et al 2013). The parameters used for the delimitation of a new species are less than 95% (AAI/ANI) and less than 70% GGDH with their closest neighbors, in conformity with the method previously described (Thompson et al 2013;De Vos et al 2017). Useful in silico phenotypes analyses were performed as previously described (Amaral et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The AAI value between D. swuensis DY59 T and D. radiopugnans ATCC 19172 T was 97% (Fig. 3b), which was higher than the 95% cut-off for distinct species [24,36]; whereas, the rest of the species had AAI values outside the species circumscription limit (Table S3). In order to further validate the wholegenome relatedness between these species, dDDH value was estimated using genome-to-genome distance calculator version 2.1 (GDGC; http:// ggdc.…”
mentioning
confidence: 87%
“…Deinococcus species have been mostly characterized employing polyphasic approach of taxonomy. Recently, it has been demonstrated that wholegenome based analyses present a reliable and reproducible tool for prokaryotic taxonomy and provide successful insights into the evolutionary relationships [19][20][21][22][23][24]. Furthermore, Deinococcus species have been reclassified as synonyms based on whole-genome analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…de/)[29]. Values of ANI, AAI and dDDH between strains HY60 T and HY54 were 99.1, 98.6 and 92.3 %, respectively, all higher than the respective threshold of 95-96[30], 95[31] and 70 %[32] for species delineation, indicating that strains HY60 T and HY54 belong to the same species (Table1). A similar conclusion was reached for strains HY82 T and HY89 as well based on the same set of scores (98.8, 98.6, 90.2%) (Table…”
mentioning
confidence: 90%